The service startup : design thinking gets lean : a practical guide to integrate design thinking and lean startup - Pinheiro, Tenny, ....- (S.l. : Hayakawa, 2014)
A practical guide to integrate Design Thinking and Lean Startup in the service era
Keywords: Design thinking